ДІАЛЕКТНА ЛЕКСИКА ЗАХІДНОГО ПОЛІССЯ: СТРУКТУРНО-СЕМАНТИЧНА ТА АРЕАЛЬНА ХАРАКТЕРИСТИКА - Євтушок, Олексій; Evtushok, A. (Волинський національний університет імені Лесі Українки, 2010)
У статті досліджені склад, лексико-семантична структура та ареальні особливості народнорозмовного словника. Проаналізовані сучасні тенденції розвитку діалектної лексики Західного Полісся. The article deals with investigation of formation and lexico-semantic structure and irreal features of folk-speech dictionary. And the modern tendencies of dialect lexicon development in the Western Ukrainian Polissya region have been analized by the author.Key words: the Western Polissya folk-speech, systemic parameters of dialect lexicon, semantic structure of the word, dialect zones, irreal sleng.
Keywords: західнополіські говірки; параметри системності діалектної лексики; семантична структура слова; діалектні зони; the Western Polissya folk-speech; systemic parameters of dialect lexicon; semantic structure of the word; dialect zones; irreal sleng